Marketing Scholarship and the Sustainable Development Goals: Thoughts on Moving Forward. Issue 2 (May 2022) - Rosenbloom, Al
This article is a commentary on how marketing scholarship can be more relevant as it tackles the human development challenges presented by the Sustainable Development Goals (SDGs). The commentary argues that as businesses are transforming themselves into purpose-driven organizations, marketing needs to be a part of that transformation. SDG 1 No Poverty and SDG 12 Sustainable Consumption and Production are discussed within the article. The commentary also tackles the institutional barriers that work against path-breaking SDG marketing scholarship: normative promotion and publication expectations along with the practitioner-academic research divide. Without realigning the incentives that reward original, boundary-spanning SDG marketing scholarship, the marketing discipline will be stuck in a cycle of rewarding one behavior while hoping for another.